Pulmonary hypertension due to acute respiratory distress syndrome - Ñamendys-Silva,S.A. (2014)
Our aims were to describe the prevalence of pulmonary hypertension in patients with acute respiratory distress syndrome (ARDS), to characterize their hemodynamic cardiopulmonary profiles, and to correlate these parameters with outcome. All consecutive patients over 16 years of age who were in the intensive care unit with a diagnosis of ARDS and an in situ pulmonary artery catheter for hemodynamic monitoring were studied. Pulmonary hypertension was diagnosed when the mean pulmonary artery pressure was >25 mmHg at rest with a pulmonary artery occlusion pressure or left atrial pressure <15 mmHg. During the study period, 30 of 402 critically ill patients (7.46%) who were admitted to the ICU fulfilled the criteria for ARDS. Of the 30 patients with ARDS, 14 met the criteria for pulmonary hypertension, a prevalence of 46.6% (95% CI; 28-66%). The most common cause of ARDS was pneumonia (56.3%). The overall mortality was 36.6% and was similar in patients with and without pulmonary hypertension. Differences in patients' hemodynamic profiles were influenced by the presence of pulmonary hypertension. The levels of positive end-expiratory pressure and peak pressure were higher in patients with pulmonary hypertension, and the PaCO2 was higher in those who died. The level of airway pressure seemed to influence the onset of pulmonary hypertension. Survival was determined by the severity of organ failure at admission to the intensive care unit.